Metaphor as fundamental to future discourse. (November 2016) - Judge, Anthony
Highlights: In a time of information overload, increasing invasiveness, and questionable strategic coherence for individuals and collectivities, the question is whether metaphors have an especially important role to play. Thinking and engaging otherwise through metaphor therefore merits particular consideration. The argument focuses on the possibility of a meta-strategy by reframing the interweaving of themes through emerging implications of "meta" and "para". This should enable forms of self-reflexive dialogue in "parameta space" to be envisaged. Abstract: In a time of information overload, increasing invasiveness, and questionable strategic coherence for individuals and collectivities, the question is whether metaphors have an especially important role to play. Thinking and engaging otherwise through metaphor therefore merits particular consideration. The argument focuses on the possibility of a meta-strategy by reframing the interweaving of themes through emerging implications of "meta" and "para". This should enable forms of self-reflexive dialogue in "parameta space" to be envisaged.